Petunidin, a B-ring 5′-O-Methylated Derivative of Delphinidin, Stimulates Osteoblastogenesis and Reduces sRANKL-Induced Bone Loss - Nagaoka, Masahiro; Maeda, Toyonobu; Moriwaki, Sawako; Nomura, Atsushi; Kato, Yasumasa; Niida, Shumpei; Kruger, Marlena C.; Suzuki, Keiko (International journal of molecular sciences, 2019)
Several lines of evidence suggest that oxidative stress is one of the key pathogenic mechanisms of osteoporosis. We aimed to elucidate the bone protective effects of petunidin, one of the most common anthocyanidins, considering its potent antioxidative activity. Petunidin (>5 μg/mL) significantly inhibited osteoclastogenesis and downregulated c-fos, Nfatc1, Mmp9, Ctsk, and Dc-stamp mRNA expression in RAW264.7 cells. Conversely, petunidin (>16 μg/mL) stimulated mineralized matrix formation and gene expression of Bmp2 and Ocn, whereas it suppressed Mmp13, Mmp2, and Mmp9 mRNA expression and proteolytic activities of MMP13 and MMP9 in MC3T3-E1 cells. Micro-CT and bone histomorphometry analyses of sRANKL-induced osteopenic C57BL/6J mice showed that daily oral administration of petunidin (7.5 mg/kg/day) increased bone volume to tissue volume (BV/TV), trabecular thickness (Tb.Th), trabecular number (Tb.N), the ratio of osteoid volume to tissue volume (OV/TV), osteoid thickness (O.Th), the ratio of osteoid surface to bone surface (OS/BS), the ratio of osteoblast surface to bone surface (Ob.S/BS), and the number of osteoblast per unit of bone surface (N.Ob/BS), and decreased trabecular separation (Tb.Sp), the ratio of eroded surface to bone surface (ES/BS), the ratio of osteoclast surface to bone surface (Oc.S/BS), and number of osteoclast per unit of bone surface (N.Oc/BS), compared to untreated mice. Furthermore, histological sections of the femurs showed that oral administration of petunidin to sRANKL-induced osteopenic mice increased the size of osteoblasts located along the bone surface and the volume of osteoid was consistent with the in vitro osteoblast differentiation and MMP inhibition. These results suggest that petunidin is a promising natural agent to improve sRANKL-induced osteopenia in mice through increased osteoid formation, reflecting accelerated osteoblastogenesis, concomitant with suppressed bone resorption.